Protection of toll-like receptor 9 against lipopolysaccharide-induced inflammation and oxidative stress of pulmonary epithelial cells via MyD88-mediated pathways - Qi, Zhenhong; He, Zhijie; Chen, Jiaxin; Ma, Mingyuan; Deng, Menghua; Zhang, Yunhai; Ma, Tianwei (Physiological research, 2022)
Acute lung injury (ALI) caused by lipopolysaccharide (LPS) is a common, severe clinical syndrome. Injury caused by inflammation and oxidative stress in vascular endothelial and alveolar epithelial cells is a vital process in the pathogenesis of ALI. Toll-like receptor 9 (TLR9) is highly expressed in LPS-induced ALI rats. In this study, Beas-2B human pulmonary epithelial cells and A549 alveolar epithelial cells were stimulated by LPS, resulting in the upregulation of TLR9 in a concentrationdependent manner. Furthermore, TLR9 overexpression and interference vectors were transfected before LPS administration to explore the role of TLR9 in LPS-induced ALI in vitro. The findings revealed that inhibition of TLR9 reduced inflammation and oxidative stress while suppressing apoptosis of LPS-induced Beas-2B and A549 cells, whereas TLR9 overexpression aggravated these conditions. Moreover, TLR9 inhibition resulted in downregulated protein expression of myeloid differentiation protein 88 (MyD88) and activator activator protein 1 (AP-1), as well as phosphorylation of nuclear factor-?B (NF-kappaB), c-Jun N-terminal kinase (JNK), and p38 mitogen-activated protein kinase (MAPK). The phosphorylation of extracellular-regulated protein kinases 1/2 was upregulated compared to that of cells subjected to only LPS administration, and this was reversed by TLR9 overexpression. These results indicate that inhibition of TLR9 plays a protective role against LPS-induced inflammation and oxidative stress in Beas-2B and A549 cells, possibly via the MyD88/NF-kappaB and MyD88/MAPKs/AP-1 pathways.
Keywords: Animals; zánět; lipopolysacharidy; Transcription Factor AP-1; oxidační stres; toll-like receptor 4; Oxidative Stress; myeloidní diferenciační faktor 88; Epithelial Cells; Myeloid Differentiation Factor 88; signální transdukce; Lipopolysaccharides; Toll-Like Receptor 9; Signal Transduction; Inflammation; toll-like receptor 9; transkripční faktor AP-1; Toll-Like Receptor 4; krysa rodu Rattus; NF-kappa B; zvířata; Acute Lung Injury; akutní poškození plic; epitelové buňky; Rats